1983
DOI: 10.3382/ps.0620537
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Selection for Body Weight and Yolk Precursor in Coturnix coturnix japonica.

Abstract: Carcass composition (protein, fat, ash, and percent dry matter), component parts, and dressing yield were determined in lines of quail undergoing divergent selection for yolk precursor, growth, or egg production. Carcass weights and yield percentages were greatest in the line selected for increased 4-week weight and lowest in the line selected for decreased 4-week weight. Carcass weights and yields were not affected by selection for yolk precursor or egg production. Carcass percent protein was lower and percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Similarly, Anna and Dariusz (2011) also reported that Pharaoh quail slaughtered at 33 days did not show any significant difference in carcass yield. In terms of dressing proportion (%) in Japanese quails (6 to 33 weeks); earlier researchers Wilson et al (1961); Bacon and Nestor (1983); El-Fiky (1991); Kosba et al (1992); Anna and Dariusz (2011) noted as 69.4%, 59.3 to 67.3%, 69.6 to 68.1% and 66.1 to 63.7% respectively. In this study; keel length (cm) differed significantly at 3, 5 and 6 weeks except week-4; indicated difference in keel length (cm) among studied quails (Table 1) are close to prior results of Rehman (2006) and Jatoi (2012) who reported that keel length (cm) differed significantly among imported and local Japanese quails stocks at week-3 while non-significant effect on week-4.…”
Section: Resultsmentioning
confidence: 90%
“…Similarly, Anna and Dariusz (2011) also reported that Pharaoh quail slaughtered at 33 days did not show any significant difference in carcass yield. In terms of dressing proportion (%) in Japanese quails (6 to 33 weeks); earlier researchers Wilson et al (1961); Bacon and Nestor (1983); El-Fiky (1991); Kosba et al (1992); Anna and Dariusz (2011) noted as 69.4%, 59.3 to 67.3%, 69.6 to 68.1% and 66.1 to 63.7% respectively. In this study; keel length (cm) differed significantly at 3, 5 and 6 weeks except week-4; indicated difference in keel length (cm) among studied quails (Table 1) are close to prior results of Rehman (2006) and Jatoi (2012) who reported that keel length (cm) differed significantly among imported and local Japanese quails stocks at week-3 while non-significant effect on week-4.…”
Section: Resultsmentioning
confidence: 90%